Question
upstudy study bank question image url

Solving Systems of Equations by Graphing Solve each swstem by graphing. \( \begin{array}{ll}\text { 1) } y=-\frac{5}{3} x+3-\frac{6}{3} x+3=\frac{1}{3} x-3 & \text { 2) } y=4 x+3 \\ y=\frac{1}{3} x-3 & x=1\end{array} \)

Ask by Gordon Gordon. in the United States
Feb 25,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The solutions are: 1. \( (0, 3) \) 2. \( (1, 7) \)

Solution

Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}y=4x+3\\x=1\end{array}\right.\) - step1: Substitute the value of \(x:\) \(y=4\times 1+3\) - step2: Simplify: \(y=7\) - step3: Calculate: \(\left\{ \begin{array}{l}x=1\\y=7\end{array}\right.\) - step4: Check the solution: \(\left\{ \begin{array}{l}x=1\\y=7\end{array}\right.\) - step5: Rewrite: \(\left(x,y\right) = \left(1,7\right)\) Solve the system of equations \( y=-\frac{5}{3} x+3; y=-\frac{1}{3} x+3 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}y=-\frac{5}{3}x+3\\y=-\frac{1}{3}x+3\end{array}\right.\) - step1: Substitute the value of \(y:\) \(-\frac{5}{3}x+3=-\frac{1}{3}x+3\) - step2: Cancel equal terms: \(-\frac{5}{3}x=-\frac{1}{3}x\) - step3: Add or subtract both sides: \(-\frac{5}{3}x-\left(-\frac{1}{3}x\right)=0\) - step4: Subtract the terms: \(-\frac{4}{3}x=0\) - step5: Change the signs: \(\frac{4}{3}x=0\) - step6: Rewrite the expression: \(x=0\) - step7: Substitute the value of \(x:\) \(y=-\frac{5}{3}\times 0+3\) - step8: Substitute back: \(y=3\) - step9: Calculate: \(\left\{ \begin{array}{l}x=0\\y=3\end{array}\right.\) - step10: Check the solution: \(\left\{ \begin{array}{l}x=0\\y=3\end{array}\right.\) - step11: Rewrite: \(\left(x,y\right) = \left(0,3\right)\) Let's solve the systems of equations step by step by graphing. ### System 1: The equations are: 1. \( y = -\frac{5}{3} x + 3 \) 2. \( y = -\frac{1}{3} x + 3 \) To find the intersection point, we can set the two equations equal to each other: \[ -\frac{5}{3} x + 3 = -\frac{1}{3} x + 3 \] By simplifying, we can see that both equations intersect at the point where \( x = 0 \). Substituting \( x = 0 \) into either equation gives: \[ y = -\frac{5}{3}(0) + 3 = 3 \] Thus, the solution for the first system is: \[ (x, y) = (0, 3) \] ### System 2: The equations are: 1. \( y = 4x + 3 \) 2. \( x = 1 \) Since the second equation is a vertical line at \( x = 1 \), we can substitute \( x = 1 \) into the first equation to find \( y \): \[ y = 4(1) + 3 = 4 + 3 = 7 \] Thus, the solution for the second system is: \[ (x, y) = (1, 7) \] ### Summary of Solutions: 1. For the first system: \( (x, y) = (0, 3) \) 2. For the second system: \( (x, y) = (1, 7) \)

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Extra Insights

To solve the first system by graphing, let's rearrange the equations. The first equation simplifies to \( y = -\frac{5}{3}x + 1 \), and the second equation is already in slope-intercept form. Now, plot both lines on a graph. The intersection point of both lines will give you the solution to the system. For the second system, we have the linear equation \( y = 4x + 3 \) and a vertical line \( x = 1 \). Substitute \( x = 1 \) into the first equation to find \( y = 4(1) + 3 = 7 \). Therefore, the solution is the point (1, 7).

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy